A non-metallic brake pad with low noise and good heat dissipation
By designing multiple arc-shaped heat dissipation grooves and specific combined materials on the brake pads, the problems of reduced braking capacity and poor thermal conductivity of the brake pads in high-temperature environments are solved, low noise, low dust and efficient heat dissipation are achieved, and service life is extended .
Patent Information
- Application Number
- CN202210097593.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-01-27
AI Technical Summary
The existing brake pads have a rapid rise in temperature due to continuous braking during downhill roads and other road conditions, which reduce the braking capacity, and have groove problems caused by poor thermal conductivity, easy brittle cracks on the edges and corners and impurities. The cost is high and the environment is unfriendly.
It uses low-noise, heat-dissipating non-metallic brake pads, made of friction material and steel back, characterized by the fact that there are multiple arc-shaped heat dissipation tanks on the front of the friction material, combined with porous titanium carbide, aluminum silicate fiber and other combination materials, through The spiral air flow takes away the hot air flow, improves heat dissipation performance, and forms the finished product through a multi-station hot press and heat treatment.
It effectively reduces the brake disc temperature, extends the service life, maintains stable braking safety and comfort, reduces noise and dust, and reduces temperature by 20% compared to conventional brake pads.
Smart Images

Figure CN114483844B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to an automobile brake pad with good heat dissipation, in particular to a non-metallic brake pad with low noise and good heat dissipation. Background Art
[0002] Brake pads are automobile brake linings, which are friction materials fixed on the brake drum or brake disc that rotates with the wheel. The friction linings and friction blocks are subjected to external pressure, generating friction effects. The friction between the brake pads and the brake drum and the tire and the ground is used to convert the kinetic energy of the vehicle into heat energy after friction, thereby achieving the effect of slowing down or stopping the vehicle. Therefore, brake pads are a vital part of the car and are related to personal safety. We found that under road conditions such as downhill mountain roads, the brakes are continuously braked, the temperature rises rapidly, and the brake disc may reach a temperature of four, five hundred or even seven hundred degrees Celsius. The braking ability of the brake pads will deteriorate and the braking distance will increase. However, in some existing technologies, the brake pads contain a large number of hard spots and impurities, which will pull out many grooves on the surface of the brake disc. In addition, the thermal decay is very serious, and there are technical problems such as poor thermal conductivity and easy brittle cracking of corners.
[0003] The company has a high-performance ternary composite brake pad (patent number 201610064026.1). Although it has good resistance to thermal decay, it uses a lot of imported materials and the process of the ternary structure is relatively complicated, so the cost is very high. Researching and developing a brake pad that is cost-controlled, harmless to the environment, and has high-efficiency heat dissipation performance has become our company's new pursuit. Summary of the invention
[0004] The object of the present invention is to provide a non-metallic brake pad with low noise and good heat dissipation to solve the problems raised in the above background technology.
[0005] A low-noise, good heat dissipation non-metallic brake pad, composed of a friction material, a base material and a steel back, characterized in that: a plurality of arc-shaped heat dissipation grooves are arranged on the front of the friction material, and the friction material comprises the following friction material components by weight: 10-15 parts of porous titanium carbide, 5-7 parts of aluminum silicate fiber, 9-11 parts of potassium hexatitanate whiskers, 6-8 parts of cashew oil friction powder, 8-10 parts of barite, 10-15 parts of diabase fiber, 9-11 parts of needle-shaped wollastonite powder, 8-11 parts of boron phenolic resin, 3-5 parts of nitrile rubber, 1-1.9 parts of melamine, 2-3 parts of magnesium oxide, 1-3 parts of zinc sulfide, 2-5 parts of silicon carbide, 2.8-5 parts of polytetrafluoroethylene, 12-17 parts of flake graphite, 9-11 parts of meteorological white carbon black; the base material includes the following friction material components in parts by weight: 6-8 parts of calcined petroleum coke, 2.5-3.3 parts of magnetite powder, 0.3-0.6 parts of nano zinc oxide, 0.3-0.5 parts of isopropyl alcohol, 12-16 parts of calcium sulfate whiskers, 10-12 parts of copper fibers, 3-5 parts of boron phenolic resin, 3-5 parts of flake aluminum powder, 5-6 parts of zircon powder, and 0.2-0.3 parts of sodium dodecyl sulfate.
[0006] Preferably, the heat dissipation grooves are arranged obliquely.
[0007] Preferably, among the heat dissipation grooves, the deep heat dissipation groove close to the end of the friction material is close to the steel back.
[0008] Preferably, the shallow heat dissipation grooves between the deep heat dissipation grooves are 1 / 5 to 1 / 4 of the deep heat dissipation grooves.
[0009] A method for preparing a brake pad, characterized in that it comprises the following steps:
[0010] A. Apply hot glue to the backing plate, and then place the backing plate on the bottom of the mold cavity;
[0011] B. Mix the base material and friction material separately and put them into the mold, with the base material located at the bottom of the friction material;
[0012] C. Pressing: Use a multi-station hot press to pressurize the mold cavity. Each hydraulic cylinder corresponds to a mold. Press with equal ratio pressure and heat the mold as a whole. After 2-3 minutes of extrusion, a molded blank is obtained. The heating and extrusion conditions can be: temperature 150-200℃, pressure 20-30MPa, and pressure holding for 5-10 minutes.
[0013] D. Finishing: polish the semi-finished products and arrange the appearance;
[0014] E. Heat treatment: The semi-finished product is sent to a heat treatment oven: baked at 160°C for 1 hour, 190°C for 1 hour, and 220°C for 2 hours, and then the oven is opened and cooled to room temperature;
[0015] F. Ablation: adopt segmented ablation, the ablation temperature is 450℃-650℃, the ablation time will vary according to different formulas, generally 4-8 minutes to obtain the finished product.
[0016] The present invention adopts multiple arc-shaped heat dissipation grooves. The brake disc can generate spiral airflow in the multiple arc-shaped grooves, carrying and throwing out the hot airflow containing dust, and combined with the porous titanium carbide, aluminum silicate fiber, flake graphite and other components, the heat dissipation performance can be further improved. In addition, the friction coefficient of the present invention is appropriate, and the friction behavior is converted from the original fatigue wear to indirect wear related to the transfer layer formed on the contact surface. The braking line is smooth and the service life of the brake disc can be extended. The base material of the present invention has good adhesion and can effectively isolate the high temperature of braking, thereby maintaining a stable braking safety distance and braking comfort. After half a year of use, it is shown that the present invention does not rust during use, has low dust and low noise, and the brake disc is bright, especially when driving on mountain roads. The friction material and the brake disc dissipate heat quickly, and the temperature is about 20% lower than that of conventional friction plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the structure of the present invention;
[0018] Figure 2 This is a wear resistance test diagram of the present invention;
[0019] Figure 3 It is the noise generation curve diagram of the present invention;
[0020] Figure 4 It is a test diagram 1 of the present invention on a brake inertia bench test machine;
[0021] Figure 5 It is a test diagram 2 of the present invention on a brake inertia bench test machine;
[0022] Figure 6 FIG3 is a test diagram of the present invention on a brake inertia bench test machine. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] like Figure 1As shown, the non-metallic brake pad with low noise and good heat dissipation is composed of a friction material 3 and a steel back 1. The front of the friction material 3 is provided with a plurality of arc-shaped heat dissipation grooves 8, and the heat dissipation grooves 8 are arranged obliquely. Among the heat dissipation grooves 8, the deep heat dissipation grooves 82 and 83 near the ends of the friction material 3 are close to the steel back. The shallow heat dissipation grooves 81 between the deep heat dissipation grooves are 1 / 5 to 1 / 4 of the deep heat dissipation grooves. The present invention adopts a plurality of arc-shaped heat dissipation grooves, and the brake disc can generate a spiral airflow in the plurality of arc-shaped grooves, carrying and throwing out the hot airflow containing dust.
[0025] Embodiment 1:
[0026] The friction material includes the following friction material components in parts by weight: 10 parts of porous titanium carbide, 7 parts of aluminum silicate fiber, 9 parts of potassium hexatitanate whisker, 8 parts of cashew oil friction powder, 8 parts of barite, 15 parts of diabase fiber, 11 parts of needle-shaped wollastonite powder, 11 parts of boron phenolic resin, 5 parts of nitrile rubber, 1.9 parts of melamine, 3 parts of magnesium oxide, 3 parts of zinc sulfide, 5 parts of silicon carbide, 5 parts of polytetrafluoroethylene, 17 parts of flake graphite, and 9 parts of meteorological white carbon black.
[0027] The base material comprises the following friction material components in parts by weight: 8 parts of calcined petroleum coke, 2.5 parts of magnetite powder, 0.6 parts of nano zinc oxide, 0.5 parts of isopropyl alcohol, 12 parts of calcium sulfate whiskers, 10 parts of copper fibers, 5 parts of boron phenolic resin, 5 parts of flake aluminum powder, 6 parts of zircon powder, and 0.3 parts of sodium dodecyl sulfate.
[0028] The brake pad preparation method comprises the following steps: A. applying hot glue on the back plate and then placing the back plate on the bottom of the mold cavity;
[0029] B. Mix the base material and friction material separately and put them into the mold, with the base material located at the bottom of the friction material;
[0030] C. Pressing: Use a multi-station hot press to pressurize the mold cavity. Each hydraulic cylinder corresponds to a mold. Press with equal ratio pressure and heat the mold as a whole. After 2-3 minutes of extrusion, a molded blank is obtained. The heating and extrusion conditions can be: temperature 150-200℃, pressure 20-30MPa, and pressure holding for 5-10 minutes.
[0031] D. Finishing: polish the semi-finished products and arrange the appearance;
[0032] E. Heat treatment: The semi-finished product is sent to a heat treatment oven: baked at 160°C for 1 hour, 190°C for 1 hour, and 220°C for 2 hours, and then the oven is opened and cooled to room temperature;
[0033] F. Ablation: adopt segmented ablation, the ablation temperature is 450℃-650℃, the ablation time will vary according to different formulas, generally 4-8 minutes to obtain the finished product.
[0034] Embodiment 2:
[0035] The friction material includes the following friction material components by weight: 12 parts of porous titanium carbide, 6 parts of aluminum silicate fiber, 11 parts of potassium hexatitanate whisker, 7 parts of cashew oil friction powder, 9 parts of barite, 12 parts of diabase fiber, 9 parts of needle-shaped wollastonite powder, 8 parts of boron phenolic resin, 3 parts of nitrile rubber, 1 part of melamine, 2 parts of magnesium oxide, 1.9 parts of zinc sulfide, 2.8 parts of silicon carbide, 3.1 parts of polytetrafluoroethylene, 12 parts of flake graphite, and 10 parts of meteorological white carbon black. The base material includes the following friction material components by weight: 6 parts of calcined petroleum coke, 3.3 parts of magnetite powder, 0.3 parts of nano zinc oxide, 0.3 parts of isopropyl alcohol, 16 parts of calcium sulfate whisker, 12 parts of copper fiber, 3 parts of boron phenolic resin, 3 parts of flake aluminum powder, 5 parts of zircon powder, and 0.2 parts of sodium dodecyl sulfate.
[0036] The brake pad preparation method comprises the following steps: A. applying hot glue on the back plate 1, and then placing the back plate 1 on the bottom of the mold cavity;
[0037] B. Mix the base material and friction material separately and put them into the mold, with the base material located at the bottom of the friction material;
[0038] C. Pressing: Use a multi-station hot press to pressurize the mold cavity. Each hydraulic cylinder corresponds to a mold. Press with equal ratio pressure and heat the mold as a whole. After 2-3 minutes of extrusion, a molded blank is obtained. The heating and extrusion conditions can be: temperature 150-200℃, pressure 20-30MPa, and pressure holding for 5-10 minutes.
[0039] D. Finishing: polish the semi-finished products and arrange the appearance;
[0040] E. Heat treatment: The semi-finished product is sent to a heat treatment oven: baked at 160°C for 1 hour, 190°C for 1 hour, and 220°C for 2 hours, and then the oven is opened and cooled to room temperature;
[0041] F. Ablation: adopt segmented ablation, the ablation temperature is 450℃-650℃, the ablation time will vary according to different formulas, generally 4-8 minutes to obtain the finished product.
[0042] Embodiment 3:
[0043] The friction material includes the following friction material components in parts by weight: 15 parts of porous titanium carbide, 5 parts of aluminum silicate fiber, 10 parts of potassium hexatitanate whiskers, 6 parts of cashew oil friction powder, 10 parts of barite, 10 parts of diabase fiber, 10 parts of needle-shaped wollastonite powder, 9 parts of boron phenolic resin, 4 parts of nitrile rubber, 1.5 parts of melamine, 2.7 parts of magnesium oxide, 1 part of zinc sulfide, 2.2 parts of silicon carbide, 2.2 parts of polytetrafluoroethylene, 15 parts of flake graphite, and 11 parts of meteorological white carbon black.
[0044] The base material comprises the following friction material components in parts by weight: 7 parts of calcined petroleum coke, 3 parts of magnetite powder, 0.5 parts of nano zinc oxide, 0.4 parts of isopropyl alcohol, 15 parts of calcium sulfate whiskers, 10.8 parts of copper fibers, 4 parts of boron phenolic resin, 4 parts of flake aluminum powder, 5.5 parts of zircon powder, and 0.25 parts of sodium dodecyl sulfate.
[0045] The brake pad preparation method comprises the following steps: A. applying hot glue on the back plate 1, and then placing the back plate 1 on the bottom of the mold cavity;
[0046] B. Mix the base material and friction material separately and put them into the mold, with the base material located at the bottom of the friction material;
[0047] C. Pressing: Use a multi-station hot press to pressurize the mold cavity. Each hydraulic cylinder corresponds to a mold. Press with equal ratio pressure and heat the mold as a whole. After 2-3 minutes of extrusion, a molded blank is obtained. The heating and extrusion conditions can be: temperature 150-200℃, pressure 20-30MPa, and pressure holding for 5-10 minutes.
[0048] D. Finishing: polish the semi-finished products and arrange the appearance;
[0049] E. Heat treatment: The semi-finished product is sent to a heat treatment oven: baked at 160°C for 1 hour, 190°C for 1 hour, and 220°C for 2 hours, and then the oven is opened and cooled to room temperature;
[0050] F. Ablation: adopt segmented ablation, the ablation temperature is 450℃-650℃, the ablation time will vary according to different formulas, generally 4-8 minutes to obtain the finished product.
[0051] test:
[0052] The present invention was placed on a brake inertia bench test machine and tested according to SAE J2522 D785 and SAE J2521 03-26-05 standards. The test results are shown in Figure 2 It can be seen that the present invention has lower wear; Figure 3 It can be seen that the brake pads have low braking noise and no squealing.
[0053] As shown in 4, 5, and 6, the friction performance index is also very superior. After half a year of use, it is shown that the present invention is rust-free, has low dust and noise, and the brake disc is bright, especially when driving on mountain roads. The friction material and the brake disc dissipate heat quickly, and the temperature is about 20% lower than that of conventional friction plates.
[0054] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A low-noise, good heat dissipation non-metallic brake pad, which is composed of friction material, base material and steel backing, and is characterized by: The front of the friction material is provided with a plurality of arc-shaped heat dissipation grooves, and the friction material comprises the following friction material components by weight: 10-15 parts of porous titanium carbide, 5-7 parts of aluminum silicate fiber, 9-11 parts of potassium hexatitanate whisker, 6-8 parts of cashew oil friction powder, 8-10 parts of barite, 10-15 parts of diabase fiber, 9-11 parts of needle-shaped wollastonite powder, 8-11 parts of boron phenolic resin, 3-5 parts of nitrile rubber, 1-1.9 parts of melamine, 2-3 parts of magnesium oxide, 1-3 parts of zinc sulfide, 2-5 parts of silicon carbide, 2.8-5 parts of polytetrafluoroethylene, 12-17 parts of flake graphite, and 9-11 parts of meteorological white carbon black; the base material comprises the following friction material components by weight: 6-8 parts of calcined petroleum coke, 2.5-3.3 parts of magnetite powder, 0.3-0.001 parts of nano zinc oxide. .6 parts, isopropyl alcohol 0.3-0.5 parts, calcium sulfate whiskers 12-16 parts, copper fibers 10-12 parts, boron phenolic resin 3-5 parts, flake aluminum powder 3-5 parts, zircon powder 5-6 parts, sodium dodecyl sulfate 0.2-0.3 parts; among the heat dissipation grooves, the deep heat dissipation grooves close to the ends of the friction material are close to the steel back; the shallow heat dissipation grooves between the deep heat dissipation grooves are 1 / 5-1 / 4 of the deep heat dissipation grooves.
2. The non-metallic brake pad with low noise and good heat dissipation according to claim 1 is characterized by: The heat dissipation slots are arranged obliquely.
3. A method for preparing a non-metallic brake pad with low noise and good heat dissipation according to any one of claims 1-2, characterized in that: The following steps are involved: A. Apply hot glue to the backing plate, and then place the backing plate on the bottom of the mold cavity; B. Mix the base material and friction material separately and put them into the mold, with the base material located at the bottom of the friction material; C. Pressing: Use a multi-station hot press to pressurize the mold cavity. Each hydraulic cylinder corresponds to a mold. Press with equal ratio pressure and heat the mold as a whole. After 2-3 minutes of extrusion, the molded blank is obtained. The heating and extrusion conditions are: temperature 150-200℃, pressure 20-30MPa, and pressure holding for 5-10 minutes; D. Finishing: polish the semi-finished products and arrange the appearance; E. Heat treatment: The semi-finished product is sent to a heat treatment oven, where it is baked at 160°C for 1 hour, 190°C for 1 hour, and 220°C for 2 hours, and then the oven is opened to cool to room temperature; F. Ablation: adopt segmented ablation, the ablation temperature is 450℃-650℃, the ablation time will vary according to different formulas, generally 4-8 minutes to obtain the finished product.
Citation Information
Patent Citations
A high-performance ternary composite brake pad
CN105909706B
Zirconium oxide modified novel high temperature resistant ceramic car disc brake pad and preparation method thereof
CN103335044A
High-performance ternary compound brake pad
CN105909706A
Low-noise high-temperature-resistant brake pad
CN106117956A
Vehicle brake pad with fast heat dissipation and excellent heat stability
CN108105298A
